2021
DOI: 10.3389/fnagi.2021.716917
|View full text |Cite
|
Sign up to set email alerts
|

Microglial TREM2 Mitigates Inflammatory Responses and Neuronal Apoptosis in Angiotensin II-Induced Hypertension in Middle-Aged Mice

Abstract: Growing evidence suggests that hypertension and aging are prominent risk factors for the development of late-onset Alzheimer’s disease (LOAD) by inducement of neuroinflammation. Recent study showed that neuroinflammation via activated microglia induces reactive astrocytes, termed A1 astrocytes, that highly upregulate numerous classical complement cascade genes that are destructive to neurons in neurodegeneration diseases. Moreover, triggering receptor expressed on myeloid cells 2 (TREM2) is considered as one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“… 53 , 54 Recently, TREM2 was reported to be significantly upregulated in microglia in a hypertension model induced by Ang II infusion, and the overexpression of microglial TREM2 mitigated the microglial inflammatory response, suggesting its possible beneficial effects on BP regulation. 55 …”
Section: The Potential Role Of Microglia In Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“… 53 , 54 Recently, TREM2 was reported to be significantly upregulated in microglia in a hypertension model induced by Ang II infusion, and the overexpression of microglial TREM2 mitigated the microglial inflammatory response, suggesting its possible beneficial effects on BP regulation. 55 …”
Section: The Potential Role Of Microglia In Cardiovascular Diseasesmentioning
confidence: 99%
“…Controversy remains regarding whether TREM2 participates in the regulation of BP. [ 55 ] Male C57BL/6 mice (25±5 g) Electric foot shock with noises induced a stressed condition RAGE knockout via Cre-CX3CR1/RAGE fl/fl mice 1. Stress exposure increased the cytoplasmic translocation of HMGB1 in microglia.…”
Section: The Potential Role Of Microglia In Cardiovascular Diseasesmentioning
confidence: 99%
“…The mouse primary microglial cultures were prepared as we previously described [ 39 , 40 ]. Briefly, cortical tissues were isolated from newborn C57BL/6 mouse pups (P1) and were dissected in ice-cold Hank’s balanced salt solution (HBSS, Corning).…”
Section: Methodsmentioning
confidence: 99%
“…Models of hypertension increased the number of activated microglia in the cortex and hippocampus of mice, upregulated triggering receptor expressed on myeloid cells 2 (TREM2) produced by microglia, and increased amyloid-beta deposition [ 102 ]. In mice with transverse aortic constriction, it was demonstrated that hypertension per se triggered neuroinflammation before amyloid-beta deposition occurred [ 103 ].…”
Section: Neuroinflammatory Sequelae Of Cardiac Disordersmentioning
confidence: 99%